2021
DOI: 10.3390/ijerph18158041
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bisphenol A Concentrations and Parameters of Ovarian Reserve among Women from a Fertility Clinic

Abstract: Background: Human exposure to environmentally widespread endocrine disruptors, especially bisphenol A (BPA), has been suggested to affect reproductive health. Animal studies indicate that BPA may play a role in the process of reproduction and impact on maturing oocytes, meiotic cell division or fertilization rate. Nevertheless, data regarding the effects of exposure to BPA on women’s ovarian function are still limited. Therefore, the aim of the current study is to assess the effects of environmental exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…The researchers also noted that BPA is negatively associated with anti-Müllerian hormone (AMH) and day-3 FSH, but no statistical significance was found [ 27 ]. Two recent studies confirmed the aforementioned data [ 47 , 50 ]. Czubacka et al, in particular, found a negative association of high BPA levels with AFC and AMH [ 47 ].…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…The researchers also noted that BPA is negatively associated with anti-Müllerian hormone (AMH) and day-3 FSH, but no statistical significance was found [ 27 ]. Two recent studies confirmed the aforementioned data [ 47 , 50 ]. Czubacka et al, in particular, found a negative association of high BPA levels with AFC and AMH [ 47 ].…”
Section: Resultssupporting
confidence: 69%
“…Two recent studies confirmed the aforementioned data [ 47 , 50 ]. Czubacka et al, in particular, found a negative association of high BPA levels with AFC and AMH [ 47 ]. Similarly, Lin et al reported a lower AFC count in the group with high BPA levels, although no statistical significance was reached [ 49 ].…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, there is some evidence that BPA affects epigenetic mechanisms such as DNA methylation and chromatin structure [ 30 ]. Some studies have revealed that elevated serum or urinary BPA levels were associated with anovulation, decreased number of antral follicle count (AFC) or lower level of anti-Müllerian hormone (AMH), and consequently infertility [ 26 , 27 , 31 ]. Due to the constant exposure, BPA possesses a real hazard to human health and has thus been banned in baby bottles in the European Union in 2011; the tolerable daily intake of BPA is considered 0.05 mg/kg bodyweight per day [ 32 ].…”
Section: Resultsmentioning
confidence: 99%